Robotic colectomy with CME versus laparoscopic colon resection with or without CME for colon cancer: a systematic review and meta-analysis - Oweira, Hani; Reißfelder, Christoph; Elhadedy, H; Rahbari, Nuh Nabi; Mehrabi, Arianeb; Fattal, Mohamad Wahid; Khan, JS; Chaouch, MA (Annals of the Royal College of Surgeons of England, 2023)
Introduction - This systematic review with meta-analysis aimed to compare the robotic complete mesocolon excision (RCME) to laparoscopic colectomy (LC) with (LCME) or without CME (LC non-CME) in postoperative outcomes, harvested lymph nodes and disease-free survival. - Methods - We performed a systematic review with meta-analysis according to PRISMA 2020 and AMSTAR 2 guidelines. - Results - The literature search yielded seven comparative studies including 677 patients: 269 patients in the RCME group and 408 in the LC group. The pooled analysis concluded to a lower conversion rate in the RCME group (OR=0.17; 95% CI [0.04, 0.74], p=0.02). There was no difference between the two groups in terms of morbidity (OR=1.03; 95% CI [0.70, 1.53], p=0.87), anastomosis leakage (OR=0.83; 95% CI [0.18, 3.72], p=0.81), bleeding (OR=1.90; 95% CI [0.64, 5.58], p=0.25), wound infection (OR=1.37; 95% CI [0.51, 3.68], p=0.53), operative time (mean difference (MD)=36.32; 95% CI [−24.30, 96.93], p=0.24), hospital stay (MD=−0.94; 95% CI [−2.03, 0.15], p=0.09) and disease-free survival (OR=1.29; 95% CI [0.71, 2.35], p=0.41). In the subgroup analysis, the operative time was significantly shorter in the LCME group than RCME group (MD=50.93; 95% CI [40.05, 61.81], p<0.01) and we noticed a greater number of harvested lymph nodes in the RCME group compared with LC non-CME group (MD=8.96; 95% CI [5.98, 11.93], p<0.01). - Conclusions - The robotic approach for CME ensures a lower conversion rate than the LC. RCME had a longer operative time than the LCME subgroup and a higher number of harvested lymph nodes than the LC non-CME group.
Online veröffentlicht: 11. August 2022
Gesehen am 01.07.2024